Mechanical Resistance on Cold Welding Achievement between Cogged Surfaces - Bogdan GEORGESCU; Valeriu GEORGESCU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2008)
Cold welding on cogged surfaces is a technology developed by researchers from Robotics and Welding Department, Dunarea de Jos University of Galati. Easily deformable samples, having plane surfaces, are pressed on cogged surfaces of harder samples. The paper presents several experimental results regarding mechanical resistance on cold welding achievement. Welded joints between aluminum and copper, brass, carbon steel, stainless steel have been obtained. The maximum mechanical strength is obtained at the deformation rates 20...30%, value obviously much lower that the one characterizing the usual cold welding (minimum 70%). While the tensile strength of the joint is low (around 10% of the tensile strength of the parent metal), the shearing strength is much relevant.